The mistletoe promise [compact disc, unabridged] - Evans, Richard Paul (Evans, Richard Paul., 2014)
Alone and distrustful after a bitter divorce, Elise surprises herself by accepting a proposition from a man who lives in her building that they pretend to be a couple for the weeks preceding the Christmas holiday.